Uncomfortable truths: Teaching about race and anti-Indigenous racism in the classroom - Cheryl Ward; Melody Morton Ninomiya; Michelle Firestone (The Australian Journal of Indigenous Education, 2025)
Anti-Indigenous racism education is often framed as a way to improve non-discriminatory care for Indigenous peoples. This study asked: What happens when anti-Indigenous racism is taken up by educators? What makes it challenging to manage in an adult classroom? What strategies are (un)successful? Ten adult educators participated—Indigenous (n = 4), White (n = 3) and non-Indigenous People of Colour (n = 3)—in either an interview or focus group. A phenomenological approach guided interpretation of participant narratives. Findings revealed persistent anti-Indigenous racist violence in adult educational settings. Successfully challenging anti-Indigenous racism required deep educator knowledge, self-awareness, cultural humility and strong facilitation skills. The traumatic toll on Indigenous educators and differing responses to resistance highlighted how racism is experienced and addressed differently by Indigenous, non-Indigenous People of Colour and White educators. This study provides empirical evidence for the need for pedagogical strategies that improve cultural safety, support educators and meaningfully confront anti-Indigenous racism in adult education classrooms.